Nitrogen Cycling of Active Bacteria within Oligotrophic Sediment of the Mid-Atlantic Ridge Flank. Issue 6 (3rd July 2018) - Reese, Brandi Kiel; Zinke, Laura A.; Sobol, Morgan S.; LaRowe, Doug E.; Orcutt, Beth N.; Zhang, Xinxu; Jaekel, Ulrike; Wang, Fengping; Dittmar, Thorsten; Defforey, Delphine; Tully, Benjamin; Paytan, Adina; et al.
ABSTRACT: Microbial ecology within oligotrophic marine sediment is poorly understood, yet is critical for understanding geochemical cycles. Here, 16S rRNA sequences from RNA and DNA inform the structure of active and total microbial communities in oligotrophic sediment on the western flank of the Mid-Atlantic Ridge. Sequences identified as Bacillariophyta chloroplast were detected within DNA, but undetectable within RNA, suggesting preservation in 5.6-million-year-old sediment. Statistical analysis revealed that RNA-based microbial populations correlated significantly with nitrogen concentrations, whereas DNA-based populations did not correspond to measured geochemical analytes. Bioenergetic calculations determined which metabolisms could yield energy in situ, and found that denitrification, nitrification, and nitrogen fixation were all favorable. A metagenome was produced from one sample, and included genes mediating nitrogen redox processes. Nitrogen respiration by active bacteria is an important metabolic strategy in North Pond sediments, and could be widespread in the oligotrophic sedimentary biosphere.